Cover Image. (16th July 2021) - Li, Hui; Niu, Nan; Yang, Jihui; Dong, Fei; Zhang, Tingrui; Li, Shasha; Zhao, Wei
Abstract : The cover image is based on the Research Article Nuclear respiratory factor 1 protects H9C2 cells against hypoxia‐induced apoptosis via the death receptor pathway and mitochondrial pathway by Hui Li et al., https://doi.org/10.1002/cbin.11619 .